أساليب تحقيق الغايات التربوية البنائية في الآيات المختومة بصيغة الرجاء في القرآن الكريم ودلالاتها التربوية: دراسة تحليلية - عبدالرازق، حمدي حسن أيوب (جامعة بني سويف - كلية التربية, 2022)
هدف البحث إلى دراسة الغايات التربوية البنائية وأساليب تحقيقها في الآيات القرآنية المختومة بـصيغة الرجاء (لعلكم ـ لعلهم)، ودلالاتها التربوية، إذ بلغت جميع الغايات (15) غاية، سبع منها كغايات بنائية، وهي: (التفكر، والتعقل، والتذكر، والتفقه، وتصحيح المسار، والتضرع، والكف)، وست كغايات وسطى، هي: (التقوى، والهداية، والحذر، والشكر، والإسلام، والإيمان بلقاء الله)، وغاياتان نهائيتان، هما: (نوال الرحمة، والفلاح)، واقتصرت الدراسة على الغايات السبع البنائية. وتوصلت الدراسة إلى عدة نتائج، من أهمها: أن لكل غاية من هذه الغايات مجموعة من الأساليب التي وردت بالآيات تسهم في تحقيقها، بلغت ستة وعشرين أسلوبا، منها ما هو مشترك بين أكثر من غاية، ومنها ما هو مختص بغاية ما، وتمثلت الأساليب المشتركة في أحد عشر أسلوبا، هي: وجود معلم ومنهج ـ توافر محتوى يتسم بـ (البصيرة ـ التمام ــ الهدى ـ الرحمة ـ التيسير) ـ توضيح الآيات (تبيين ـ تفصيل ـ تصريف ـ توصيل ـ تجريب) ـ الإنذار والوعيد ـ الثواب والعقاب ـ الوعظ ـ الوصية ـ ضرب الأمثال ـ التقوى ـ الطاعة والاتباع ـ العبادة والبر، وأكثر الأساليب المشتركة في تحقيق الغايات، هو أسلوب (توضيح الآيات بتبيينها وتفصيلها وتصريفها وتوصيلها وتجريبها)، إذ جاء سبع عشرة مرة باعتباره أسلوبا مشتركا مسهما في تحقيق (8) غايات تربوية، هي: التذكر، والتفقه، والتعقل، والتفكر، وتصحيح المسار، والتقوى، والهدى، والإيمان بلقاء الله. وتوصي الدراسة أن يكون التركيز في إعداد المناهج والكتب الدراسية على التعليل وبيان الفوائد والتوظيف الحياتي، حتى يكون هذا مسهما في تربية (العقل) على مهارة (التعقل)، وضرورة الاهتمام بتدريب المعلمين على كفايات (التبيين)، وأهمها: الفصاحة والبيان وامتلاك الثروة اللغوية التي تكفيهم لتوضيح الدلائل والمعارف وغيرها، وأن تركز نظم التربية والتعليم في مرحلة الطفولة على إتقان الطفل لغة التعلم وفهمها باعتبارها أداة التعلم، دون أن يتم إضعافها بتداخلها مع لغات أخرى، وأن يكون لكل شهادة من الشهادات (مدة صلاحية) لا ينتقل المتعلم للأعلى منها بعد انقضاء المدة، إلا إذا اجتاز اختبارا للتأكد من تذكره وفهمه لما درسه، وأن يشتمل المحتوى التعليمي على خصائص (البصيرة ـ الهدى ـ الرحمة ـ التيسير)، وضرورة أن يكون معلم اللغة من أهلها، لتتحقق خاصية (التيسير) فتتحقق غاية (التذكر). This study aimed to explore the methods of accomplishing formative educational goals in the Qur'anic verses sealed with the style of hopefulness state (perhaps you would لعلكم - perhaps they would لعلهم) and their educational implications. There exist fifteen educational goals, of which there are seven formative educational goals, i.e., giving thought- using reason, remembering, understanding, repenting and accepting Islam, believing with humility and stopping evil actions. In addition, there are six intermediate goals, i.e., attaining piousness, finding the way to your righteous Islamic destination, awareness of evils, thanking Allah, submitting to the will of Allah and believing in meeting Allah. Also, there are two final goals, i.e., obtaining the mercy of Allah and succeeding. The study was restricted to the seven formative goals. Among the most important findings revealed by the study were the following: Each one of these goals has a set of methods mentioned in the Qur'anic verses that contribute to achieving them which reached twenty six methods. There are common methods for achieving more than one goal while some of them are specific to a certain goal. The eleven common methods are as follows: the presence of a curriculum and teacher, availability of a content characterized with: (enlightening with the pros, perfection, enlightening with the cons, receiving the mercy of Allah, facilitation), clarification of the Qur'anic verses(making perfectly clear, explaining in details, particularizing the verses, conveying, experimenting), warning, reward and punishment, admonishing, commanding, presenting examples, piousness, obedience to Allah, worshiping Allah. The most common method for achieving goals is the method of clarification of the Qur'anic verses through (making perfectly clear, explaining in details, detailing the verses, conveying, experimenting). This method was repeated seventeen times and contributed to achieving eight educational goals, i.e., remembrance, understanding, prudence, contemplation, repenting and accepting Islam, attaining piousness, enlightening with the cons, belief in meeting Allah. The study recommended that the focus in preparing curricula and textbooks should be on showing reasons, explaining the benefits and mastering life skills, so as to contribute to educating the mind on prudence. Additionally, the study showed the necessity of paying attention to train the teachers on the competencies of clarification, the most important of which are: eloquence and possession of linguistic wealth which enable them to clarify evidence and knowledge. Also, educational systems in the childhood stage should focus on helping children master and understand the language as instrument to learning, without diminishing it through overlapping with other languages. Each certificate should have a (validity period) so that the learner does not move to the higher stage of it unless the period elapses, and he/ she passes a test to ensure that he remembers and understands what he/ she studies. . Also, educational content should be characterized with: enlightening with the pros, enlightening with the cons, receiving the mercy of Allah and facilitation), and the language teacher should be native speaker in order for the (facilitation) characteristic to be realized and the goal of (remembering) to be achieved.
Keywords: القرآن الكريم -- الآيات القرآنية -- التربية الإسلامية -- الأهداف التربوية البنائية